STUDI PENGARUH ELEMENT SIZE PADA ANALISIS ELEMEN HINGGA TERHADAP DISTRIBUSI TEGANGAN PADA KASUS FRAKTUR TULANG TIBIA - Afif Hiranda; Hilwah Nora; Syarizal Fonna; Syifaul Huzni (Prosiding Seminar Nasional USM, 2019)
Tibia is the second largest bone which is a leg strengthening bone, which connects the knee with the ankle. In carrying out its duties, the tibia receives a great load to hold the weight of the human body. In certain cases, the tibia is susceptible to failure due to activities carried out by humans. Therefore, it is necessary to estimate the effect of the load on the strength of tibia. The purpose of this study is to analyze the distribution of stress on tibia, under stand-position. The model of tibia is analyzed using ANSYS software, which is based on the finite element method. The load given to the tibia model is 400 N on the lateral condyle section, with the assumption that the human body weight is 70 kg. Fixed support is given in the medial malleolus section. Three mesh sizes used in this study are coarse mesh, medium mesh, and fine mesh. From the finite element analysis result, it was shown that the Von Misses stress obtained from coarse mesh are higher compare to medium mesh and fine mesh.